2005
DOI: 10.1590/s1517-83822005000300006
|View full text |Cite
|
Sign up to set email alerts
|

Production of xylanase and CMCase on solid state fermentation in different residues by Thermoascus aurantiacus miehe

Abstract: The use of waste as raw material is important for government economy and natural balance. The purpose of this work was to study the production of CMCase and xylanase by a Brazilian strain of Thermoascus aurantiacus in solid state fermentation (SSF) using different agricultural residues (wheat bran, sugarcane bagasse, orange bagasse, corncob, green grass, dried grass, sawdust and corn straw) as substrates without enrichment of the medium and characterize the crude enzymes. The study of the extracellular cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 28 publications
8
72
1
10
Order By: Relevance
“…The moisture present in the solid state fermentation should be sufficient for microorganism development without compromising substrate porosity. A reduced moisture content impairs the fungal accessibility of the medium nutrients, resulting in decreased microbial metabolic activity; in contrast, high concentrations of water favor bacterial contamination and reduce solid matrix porosity, compromising oxygen diffusion and metabolic heat dissipation (DA-SILVA et al, 2005;SADAF and KHARE, 2014). This supports the profile of enzyme production observed in this study ( Figure 1C).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The moisture present in the solid state fermentation should be sufficient for microorganism development without compromising substrate porosity. A reduced moisture content impairs the fungal accessibility of the medium nutrients, resulting in decreased microbial metabolic activity; in contrast, high concentrations of water favor bacterial contamination and reduce solid matrix porosity, compromising oxygen diffusion and metabolic heat dissipation (DA-SILVA et al, 2005;SADAF and KHARE, 2014). This supports the profile of enzyme production observed in this study ( Figure 1C).…”
Section: Resultssupporting
confidence: 85%
“…Thus, the T. aurantiacus strain recently isolated from the region of Dourados-MS has considerable potential for the production of xylanase in low-cost culture media (agro-industrial residues). Previous studies have confirmed the potential to produce xylanase by different strains of the same species isolated from other regions (KALOGERIS et al, 1998;DA-SILVA et al, 2005;BRIENZO et al, 2012).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations